1999
DOI: 10.1007/s003300050629
|View full text |Cite
|
Sign up to set email alerts
|

The pseudocapsule in hepatocellular carcinoma: correlation between dynamic MR imaging and pathology

Abstract: Nodular hepatocellular carcinoma (HCC) is characterized by the presence of a pseudocapsule (constructed usually from connective fibrous tissue) that appears hypointense on T1- and T2-weighted spin-echo (SE) and gradient-echo (GE) MR imaging sequences without a contrast medium. The presence of vascular structures inside the tumor, which are verified by histological exam, affects enhancement of the PC after administrating the contrast medium: The impregnation is more evident in the dynamic study but also persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 13 publications
0
69
1
1
Order By: Relevance
“…On imaging, the capsule is seen as a low-attenuating/hypointense ring on arterial phase and high-attenuating/hyperintense ring on delayed phase images (13,15) (Fig. 1).…”
Section: Capsulementioning
confidence: 99%
See 1 more Smart Citation
“…On imaging, the capsule is seen as a low-attenuating/hypointense ring on arterial phase and high-attenuating/hyperintense ring on delayed phase images (13,15) (Fig. 1).…”
Section: Capsulementioning
confidence: 99%
“…1). The microvessels in the capsule are thought to be responsible for the late enhancement because of slow flow (13,15).…”
Section: Capsulementioning
confidence: 99%
“…Secondly, the tumor grew invasively, so that the normal hepatic cell and the tumor cell interlaced with each other at the borderline. Grazioli et al [6] reported that the tumor without fibrous pseudo-capsule lacked fibrous connective septum between carcinomatous tissue and normal hepatic parenchyma histologically, carcinomatous tissue and normal hepatic parenchyma interlaced each other without obvious borderline. After enhancement, especially in the portal venous phase, the adjacent hepatic parenchyma was enhanced obviously, in contrast, the lesion were enhanced slightly.…”
Section: The Ct Appearance Of the Border Of Lesionsmentioning
confidence: 99%
“…This classification was made on the basis of accepted findings and experience with the use of MRI in human patients. 23,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] For each patient, the characterization of the lesion by MRI was correlated with the histopathology or cytology results. For animals in which a biopsy or an aspiration of a lesion was performed before MRI (n ϭ 26), the location of the specific lesion was recorded for comparison with the location of the lesion on MRI.…”
Section: Mri Analysismentioning
confidence: 99%
“…Additionally, in one animal, a thin hypointense rim was noted around the tumor, which is characteristic of a capsule or pseudocapsule that, in humans, has been confirmed on histopathology. 22,52,65 The ability to estimate tumor grade on the basis of contrast enhancement is commonly reported in human medicine but has not been described previously in veterinary medicine. 22,65 Dynamic contrast administration provides clinicians with additional useful information about specific lesions and enables lesion examination during 3 phases: arterial (20-30 seconds postinjection), portal (1 minute postinjection), and delayed or equilibrium (3-5 minutes postinjection).…”
Section: Fig 2 (A)mentioning
confidence: 99%